Bloom Anderson's Taxonomy-Based Cognitive Level Analysis of Grade 10 Interactive Mathematics Book Questions - Samsudi, Moh; Gafrillia, Annisa Lathifa; Hazarika, Anurag (Journal of Teaching and Learning Mathematics, 2024)
This research examines the distribution of cognitive abilities within the interactive mathematics textbook designed for 10th-grade students. The study recognizes the significance of mathematics education in nurturing students' cognitive skills. However, it also acknowledges the presence of ineffective methods that impede students' grasp of concepts and their capacity to solve problems. Employing a qualitative research approach, the study identifies and resolves questions in the interactive mathematics book. It explains each cognitive skill used to solve these questions and categorizes these skills according to Bloom's taxonomy. The findings reveal an uneven allocation of cognitive skills in both chapters. Questions falling under the application category (C3) are predominant, while those demanding higher-order thinking, such as creation (C6), are limited in number. This lack of diversity and balance underscores the necessity for incorporating a broader array of questions spanning various cognitive levels. The interactive mathematics book for 10th-grade students enhances comprehension and reinforces core principles. Nevertheless, it necessitates refinement in cognitive skill distribution, especially by including more questions that require advanced thinking. Rectifying this disparity would empower the book to foster students' critical thinking and problem-solving skills.